2019
DOI: 10.1186/s12872-018-0979-x
|View full text |Cite
|
Sign up to set email alerts
|

Why complicate an important task? An orderly display of the limb leads in the 12-lead electrocardiogram and its implications for recognition of acute coronary syndrome

Abstract: BackgroundIn the standard ECG display, limb leads are presented in a non-anatomical sequence: I, II, III, aVR, aVL, aVF. The Cabrera system is a display format which instead presents the limb leads in a cranial/left-to-caudal/right sequence, i.e. in an anatomically sequential order. Lead aVR is replaced in the Cabrera display by its inverted version, −aVR, which is presented in its logical place between lead I and lead II.Main textIn this debate article possible implications of using the Cabrera display, inste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…3,4 The lead aVR is often ignored in clinical practice. 5 However, different studies have shown that ST elevation in lead aVR can predict adverse events in NSTEMI patients more accurately. 6,7 Furthermore, ST elevation in aVR is a simple and an easy indicator of left main stem (LMS) or triple vessel disease (3VCAD) and can guide for the triage of these highrisk patients.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The lead aVR is often ignored in clinical practice. 5 However, different studies have shown that ST elevation in lead aVR can predict adverse events in NSTEMI patients more accurately. 6,7 Furthermore, ST elevation in aVR is a simple and an easy indicator of left main stem (LMS) or triple vessel disease (3VCAD) and can guide for the triage of these highrisk patients.…”
Section: Introductionmentioning
confidence: 99%
“…Except for some rare current occurrences (Dower et al 1990, Sgarbossa et al 2004, Case and Moss 2010, Lam et al 2015, Lindow et al 2019, neither the Cabrera sequence nor its extension to a circle seem to be in widespread use. We hope, that the proposed Cabrera Circle together with the open-source software provided given will help to further extend the use of this methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Although the programmers allow to test the PCM, ICD and CRT instruments functionality, they are not adapted to more complex simulations, such as pacemakers generated pulses measurement and visualization, its response to various states, evaluation of time intervals and synchronization of the intrinsic cardiac activity and finally the pacemaker activity in real-time [28,29]. These options would be useful for demonstration of a pacemaker function, mainly for academic and educational purposes -simulation of pathological states of the electrical conduction system of the heart-and scientific purposes -improving the design of new adaptive algorithms for pacemakers -.…”
Section: Introductionmentioning
confidence: 99%